O Gregório vai à sala de aula: a construção discursiva da argumentação na escola por meio de vídeos de repercussão midiática - Ronan José Gomes (2024)
This research addresses the teaching of argumentation at school from an interactional, discursive and dialogical perspective, as an object of Portuguese language teaching. The central objective was to develop a didactic learning project based on media coverage videos, especially with support from the Greg News program, to teach argumentative strategies, thus contributing to the formation of discursive skills in students. The proposal was motivated by the widely publicized fact that a large proportion of students’ complete elementary school without consolidating argumentative skills, and even without basic knowledge about how this discourse works. It was also motivated by the anguish experienced from years in the classroom teaching and witnessing the shortcomings presented by students in their learning, accompanied by this teacher's desire to seek professional development in the area of activity with a view to improving teaching practices and learning. Another motivation comes from the historical moment in which, immersed as societies are in digital cultures, schools urgently need to adapt to new contexts and paradigms of information and communication, given the new demands for citizenship training that the moment presents. The question that guided this work was: How to develop a teaching project using videos to contribute to the development of discursive-argumentative skills in students? To obtain answers, this work followed the characteristic path of qualitative research, of intervention to be applied at a later time, given that practice followed by reflection is its most important characteristic. The educational product of this research consists of a didactic project divided into four didactic modules composed of reading, analysis and written production workshops, based on media videos and a cartoon, and a final proposal for oral production in free debate. The theoretical framework of this research is based on studies on argumentation in the speech of Ruth Amossy (2020), on the theories of argumentation and rhetoric of Chaim Perelman and Olbrechts-Tyteca (2005) and Reboul (1998), on the dialogical perspective of language by Bakhtin (1997, 2006), in the interactional perspective of argumentation by Christian Plantin (2008) and in the studies of argumentation as a social practice by Piris (2021), in addition to Fiorin (2018).